Environmental Performance Of High-Rise Apartment’s Façade In Penang, Malaysia - Arab, Yasser (2018)
Rapidly growing population in urban areas since the 1950s causes highly increasing demands for housing units. This study aims to investigate the heat gain of the apartments’ façade design in line with the Green Building Index (GBI) standards in Malaysia. This study analyses the shading performance of high-rise apartments’ façades in Penang, Malaysia as case studies. The analysis includes six residential buildings of different architectural periods of construction in the eastern part of Penang Island. The selected case studies are Halaman Kristal 5 and Mutiara Idaman 1 from 1970s to 1990s, Halaman Kristal 1 and Mutiara Idaman 2 from 1990s to 2010s, and Baystar and the Light Linear from 2010 to present. Three different variables were measured in this survey, the façade surface temperature (℃) using thermal imager Fluke Ti20, the Overall Thermal Transfer Value (OTTV) (W/m2), and the extent of sunlight penetration (mm) using SunTool software for the computer simulation. The obtained results revealed that Halaman Kristal 1 façade design has the lowest surface temperature followed by The Light Linear, Baystar, Mutiara Idaman 2, Mutiara Idaman 1, and Halaman Kristal 5 of a modern façade architectural style. The OTTV results revealed that all case studies have an OTTV ranging from 31 to 33 W/m2 which is accepted based on Malaysian standards except for Mutiara Idaman 2 with 60 W/m2 above the acceptable standards. Regarding the shading performance, the post-modern architectural style achieved the best results of sunlight penetration followed by neo-minimalist and modern façade architectural styles.